Strength and Fracture Studies Of Steam Turbine Blade - Kaushik, Rahul (My University, 2009)
Turbines are the key devices for power generation. These are the source for converting the energy into electrical energy. Turbine blades are main component which rotates under fluid flow, which causes the conversion of potential/kinetic energy to convert into electrical energy. The sound stability of the turbine blades is essential to achieve the target. During exposure to adverse condition it may lead to formation of cracks either by corrosion or by erosion. In the present work attempt has been made to locate the cause of failure of the blade of steam turbine. The blade was made of corrosion-resistant high alloy steel of standard grade ASTM A 743 CA 6 NM. In order to do the failure analysis samples were taken from Bharat Heavy Electrical Ltd. Haridwar. The samples were characterized by different characterization techniques like tensile testing, impact testing, hardness testing, chemical analysis, optical microscopy, scanning electron microscopy, energy dispersive spectroscopy, X-ray diffraction technique. Metallographic samples were sectioned from the blade using of cut-off wheel machine (ensuring water cooling during cutting). Five samples were analysed but data of which were taken from three different blades of same turbine are presented. For microstructural examinations, the samples were ground and polished to a mirror like surface by use of metallographic grinding and polishing machines, respectively. The polished samples were etched using Villella’s etchant for about 5–15 seconds. For SEM Analysis, the sample was cut from fractured surface of the turbine blade left and the metallographic sample was prepared until polishing stage. Microstructural characterization involved use of scanning electron microscope (SEM) and an optical microscope lined with a computerized image analyzer. By the microscopy we observed that the structure was tempered martensitic. The ductile dimples were confirmed from the scanning electron microscope study. By XRD technique, α iron phase was confirmed. The failure mode was of intergranular type. The material has failed because of inclusion present in it. The details of this analysis are given in the subsequent chapters.
M.Tech. (Materials Science and Engineering)
Keywords: Trubine Blade, Failure Studies